Peran Kepemimpinan Kepala Madrasah dalam Meningkatkan Disiplin Guru Di Madrasah - Kibtiyah, Maryatul (Al-Miskawaih: Journal of Science Education, 2022)
This study aims to describe the leadership role of the Madrasah Head in improving teacher discipline at MTs Nurul Iman, Ulu Gedong Village. The focus of this research is why the leadership role of the Madrasah Head in improving teacher discipline at MTs Nurul Iman Ulu Gedong Village is not optimal? This study uses qualitative-descriptive, with the aim of being able to explore the natural state or natural setting of the research location. This study found that the implementation of the leadership of the Head of MTs Nurul Iman, Ulu Gedong Village, is marked by several efforts; (a) maintaining the interests and goals of the school, (b) group cooperation in achieving school goals, (c) a sense of equality of rights and equal obligations, (d) suggestions, opinions and criticisms, (e) freedom to subordinates to work and develop and , (f) deliberation approach. The leadership of the madrasah principal in improving teacher discipline at MTs Nurul Iman, Ulu Gedong Village was not optimal because the vision of the madrasa principal in work discipline had not been understood urgently by the teacher. An indicator of this can be seen in the presence of some teachers who are less disciplined in carrying out school regulations that have been mutually agreed upon. Penelitian ini bertujuan untuk menggambarkan  peran kepemimpinan Kepala Madrasah dalam meningkatkan disiplin guru di MTs Nurul Iman Kelurahan Ulu Gedong. Fokus penelitian ini adalah mengapa peran kepemimpinan Kepala Madrasah dalam meningkatkan disiplin guru di MTs Nurul Iman Kelurahan Ulu Gedong belum optimal? Penelitian ini menggunakan kualitatif-deskriptif, dengan maksud agar bisa memengeksplorasi keadaan yang natural atau setting alamiah dari lokasi penelitian. Penelitian ini menemukan bahwa pelaksanaan kepemimpinan Kepala MTs Nurul Iman Kelurahan Ulu Gedong ditandai dengan beberapa upaya antara lain; (a) menjaga kepentingan dan tujuan sekolah, (b) kerja sama kelompok dalam pencapaian tujuan sekolah, (c) rasa persamaan hak dan persamaan kewajiban, (d) saran, pendapat dan kritik, (e) kebebasan kepada bawahan untuk bertugas dan berkembang dan, (f) pendekatan musyawarah. Kepemimpinan kepala madrasah dalam meningkatan disiplin guru belum optimal karena visi kepala madrasah dalam disiplin kerja belum dipahami secara urgen oleh guru. Indikator hal itu terlihat pada adanya sebagian guru yang kurang disiplin dalam menjalankan peraturan sekolah yang sudah disepakati bersama.